Royal College of Music: Carbon Management Plan - Aida Berhamovic (Universitas Diponegoro, 2023)
In Autumn 2021, an updated carbon management plan was approved by Royal College of Music Council which set an ambitious goal for the Royal College of Music to achieve carbon net-zero by 2035. This plan was supported by a heat decarbonisation plan and energy assessment, which highlighted short and long-term projects that need to be undertaken for the Royal College of Music to make the transition to net zero. From this the Royal College of Music were able to develop a high- level cost and programme plan for the works required to implement these projects. The plan also aims to reduce emission arising from ‘scope 3’ of the Greenhouse Gas Protocol [1], which make up a large part of the College’s total emissions.